Experimental evolution of an alternating uni- and multicellular life cycle in Chlamydomonas reinhardtii - Ratcliff, William C.; Herron, Matthew D.; Howell, Kathryn; Pentz, Jennifer T.; Rosenzweig, Frank; Travisano, Michael (Nature communications, 2013)
The transition to multicellularity enabled the evolution of large, complex organisms, but early steps in this transition remain poorly understood. Here we show that multicellular complexity, including development from a single cell, can evolve rapidly in a unicellular organism that has never had a multicellular ancestor. We subject the alga Chlamydomonas reinhardtii to conditions that favour multicellularity, resulting in the evolution of a multicellular life cycle in which clusters reproduce via motile unicellular propagules. While a single-cell genetic bottleneck during ontogeny is widely regarded as an adaptation to limit among-cell conflict, its appearance very early in this transition suggests that it did not evolve for this purpose. Instead, we find that unicellular propagules are adaptive even in the absence of intercellular conflict, maximizing cluster-level fecundity. These results demonstrate that the unicellular bottleneck, a trait essential for evolving multicellular complexity, can arise rapidly via co-option of the ancestral unicellular form. The early steps in the evolution of multicellularity are poorly understood. Here, Ratcliff et al . show that multicellularity can rapidly evolve in the green alga Chlamydomonas reinhardtii , demonstrating that single-cell developmental bottlenecks may evolve rapidly via co-option of the ancestral phenotype.